Ulceration of the ileum in Crohn's disease: correlation with vascular anatomy. Issue 12 (December 1997) - Anthony, A; Dhillon, A P; Pounder, R E; Wakefield, A J
Abstract : BACKGROUND: Ileal ulcers in Crohn's disease tend to lie along the same side of the bowel wall as the mesenteric attachment; the mesenteric and antimesenteric borders are supplied by short and long arteries, respectively. AIM: To examine the localisation of ileal Crohn's ulcers and to test the hypothesis that predilection of Crohn's ulcers for the ileal mesenteric margin is explained by the existence of end arteries that supply the mesenteric margin. METHODS: The localisation of ulcers in the bowel wall was examined in eight resection specimens of Crohn's disease of the terminal ileum. The vascular anatomy of normal terminal ileum (n = 8) and proximal jejunum (n = 8) postmortem specimens was studied; isolated long and short vessels were ligated before perfusion in four of these specimens. RESULTS: All eight specimens of Crohn's disease of the terminal ileum showed longitudinal ulceration along the mesenteric margin. In the postmortem study, the submucosal vascular plexus derived from ileal, but not jejunal short vessels, comprised end arteries with little or no communication with the submucosal plexus arising from long vessels. Prior ligation of ileal, but not jejunal, short vessels resulted in a filling defect of the submucosal plexus along the mesenteric margin in three of the four specimens. Ligation of ileal and jejunal long vessels did not affect carbon ink perfusion of the bowel wall. CONCLUSIONS: In the human terminal ileum, the short vessels supplying the mesenteric margin are end arteries, and their pathological occlusion might cause ischaemia of this region. These findings support a vascular hypothesis for Crohn's disease and may explain, in part, both the ileal and mesenteric distribution of Crohn's disease ulcers.